Concessions to PPC? - Bart Wiegmans; Maarten Kievits; Tejo Spit (European Regional Science Association (ERSA), 2005)
Public private cooperation (further PPC) is frequently presented as the solution for budgetary shortages for governments at national and regional level. A PPC invests in infrastructure whereby efficient cooperation enables advantages for both public and private parties is claimed. It proves to be difficult to really interest private businesses for investments in infrastructure. Therefore, the central question, which we answer in this paper, is: 'From a theoretical perspective, is PPC an option for investments in infrastructure?' In this paper, a literature review is presented on the subject of public private cooperation for the development of infrastructure projects. The main findings are that firstly, there is a large diversity in projects that might qualify for PPC. More specific, each infrastructure project is unique, making it even more difficult to implement cooperation. Secondly, the role of the national and regional governments in financing infrastructure is changing. This changing role means that the governments withdraw themselves on core functions and that they strive for private party risk-bearing in infrastructure investments. Thirdly, the theoretical definition of PPC and the more practical definition differ. In Europe, most PPCs are worked out as a concession (and therefore not a real PPC). Fourthly, from a cost point of view it is possible that the government is more efficient in cost terms and the private party is more efficient in terms of turnover. Fifthly, there are several reasons for the government to interfere in economic living. Reasons concerning infrastructure might be the public goods characterise and the external impacts. Sixthly, the public characteristics of infrastructure are decreasing. Seventhly, in general it is unattractively for private parties to invest in infrastructure. In order to make it more attractive, profits can be offered to the private parties. However, this will increase the total costs of the project. Eighthly, process management shows that it is no simple task to turn a PPC into a success. When the participating parties are persuaded of the advantages that the cooperation between public and private parties can offer, have chosen consciously for the PPC, and are prepared to invest in cooperation for the long-term, then PPC can offer means to pursue the defined objectives. If true cooperation is aimed for, costs, risks, and profits must be shared instead of divided. The joint venture can provide insights into the process of sharing. Ninthly, the construction businesses are production ventures, whereas banking services and the government operate in the service industry. Finally, the market of the most important private parties that are involved in PPC is an oligopoly. This suggests quite some market power for the private businesses involved.
Keywords: 330